2012
DOI: 10.1016/j.jacc.2012.02.071
|View full text |Cite
|
Sign up to set email alerts
|

Scaring Myocardial Scars

Abstract: Despite the impressive development of medical therapies for patients with myocardial dysfunction, sudden cardiac death (SCD) is still too frequent. In patients with severe cardiomyopathies the insertion of an implantable cardiac defibrillator (ICD) has been shown to reduce SCD risk (1). For primary prevention in patients with left ventricular ejection fraction (LVEF) below 35%, ICD is now recommended (2). However, only 30% to 50% of implanted patients received appropriate ICD firings, and up to 25% suffered fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The authors concluded that myocardial scarring detected by CMR is an independent predictor of adverse outcomes in patients being considered for ICD placement. The study results were further discussed by Mewton and Chevalier (152). …”
Section: Cardiac Imagingmentioning
confidence: 86%
“…The authors concluded that myocardial scarring detected by CMR is an independent predictor of adverse outcomes in patients being considered for ICD placement. The study results were further discussed by Mewton and Chevalier (152). …”
Section: Cardiac Imagingmentioning
confidence: 86%
“…Take the STTC as an example. Te ST segment myocardial infarction (STEMI) is refected in ST elevation [46]. ST elevation is linked to infarction and can be preceded by changes indicating ischemia, such as ST depression or the T waves inversion, according to [47].…”
Section: Performance Analysismentioning
confidence: 99%